Developing Treatments for Pulmonary Arterial Hypertension. (1st January 2013) - Wilkins, Martin R.
Abstract : Developing new treatments for pulmonary arterial hypertension (PAH) is a challenge. We have enjoyed success with regulatory approvals for three drug classes—prostanoids, endothelin receptor antagonists and phosphodiesterase type 5 inhibitors. But we have also seen some disappointing results, for example, from studies with vasoactive intestinal polypeptide, statins and tergolide. Animal models are an unreliable predictor of efficacy in humans. The best model for the disease is the patient. This review discusses three major issues facing the evaluation of drugs in PAH patients—target validation, choosing the right dose, and early trial design.